Sivelestat Alleviates Atherosclerosis by Improving Intestinal Barrier Function and Reducing Endotoxemia - Nie, Hezhongrong; Xiong, Qingquan; Lan, Guanghui; Song, Chunli; Yu, Xiaohong; Chen, Lei; Wang, Daming; Ren, Tingyu; Chen, Zeyan; Liu, Xintong; Zhou, Yiwen (Frontiers in Pharmacology, 2022)
Emerging evidence suggests that atherosclerosis, one of the leading phenotypes of cardiovascular diseases, is a chronic inflammatory disease. During the atherosclerotic process, immune cells play critical roles in vascular inflammation and plaque formation. Meanwhile, gastrointestinal disorder is considered a risk factor in mediating the atherosclerotic process. The present study aimed to utilize sivelestat, a selective inhibitor of neutrophil elastase, to investigate its pharmacological benefits on atherosclerosis and disclose the gastrointestinal–vascular interaction. The activation of intestinal neutrophil was increased during atherosclerotic development in Western diet-fed ApoE-/- mice. Administration of sivelestat attenuated atherosclerotic phenotypes, including decreasing toxic lipid accumulation, vascular monocyte infiltration, and inflammatory cytokines. Sivelestat decreased intestinal permeability and endotoxemia in atherosclerotic mice. Mechanistically, sivelestat upregulated the expression of zonula occludens-1 in the atherosclerotic mice and recombinant neutrophil elastase protein-treated intestinal epithelial cells. Meanwhile, treatment of sivelestat suppressed the intestinal expression of inflammatory cytokines and NF-κB activity. In contrast, administration of lipopolysaccharides abolished the anti-atherosclerotic benefits of sivelestat in the Western diet-fed ApoE-/- mice. Further clinical correlation study showed that the circulating endotoxin level and intestinal neutrophil elastase activity were positively correlated with carotid intima-medial thickness in recruited subjects. In conclusion, sivelestat had pharmacological applications in protection against atherosclerosis, and intestinal homeostasis played one of the critical roles in atherosclerotic development.